Acute toxicity evaluation of a crude sap isolated from Nypa fruticans Wurmb. in Sprague Dawley rats - Siti Fatimah Roqiah Yahaya,; Niza Samsuddin,; Suhana Mamat,; Rozita Hod,; Nor Zamzila Abdullah,; Nor Azlina A Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nypa fruticans Wurmb. (nipa palm) sap, locally known as air nira or tuak, is a sweet natural beverage in Malaysia with antioxidant potency beneficial for human health. However, nypa sap lacks scientific attention with no toxicity study has been established. Therefore, this study was performed to evaluate the acute toxicity of nypa sap in the female Sprague Dawley rats. Twenty-five female rats were randomly divided into one control group and four treated groups. Treated groups were orally administered with doses of 5, 50, 300, and 2000 mg/kg of nypa sap, while the control group had received normal saline solution. The animals’ vital signs and mortality were recorded daily at an interval of 30 min and continued up to 14 days. Their blood samples and organs were harvested for toxicity analysis to assess liver and kidney function, lipid profile, and full blood count. The acute toxicity test via measurement of the biochemical and haematological parameters had shown that there was no significant difference between the treated and control groups. However, the blood glucose level in the treated groups (at higher doses of 300 and 2000 mg/kg, respectively) was significantly decreased. A similar trend was recorded for mean corpuscular volume (MCV) albeit in the treated group of 50 mg/kg doses. Histopathological examination of the organs showed no signs of abnormality in both treated and untreated groups. Overall, the results showed that consumption of nypa sap is potentially safe with no acute toxic effect on the laboratory rat models.